2017
DOI: 10.1186/s12936-017-1827-7
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Plasmodium falciparum mature gametocyte-infected erythrocytes by antibodies of semi-immune adults and malaria-exposed children from Gabon

Abstract: BackgroundTransmission of malaria from man to mosquito depends on the presence of gametocytes, the sexual stage of Plasmodium parasites in the infected host. Naturally acquired antibodies against gametocytes exist and may play a role in controlling transmission by limiting the gametocyte development in the circulation or by interrupting gamete development and fertilization in the mosquito following ingestion. So far, most studies on antibody responses to sexual stage antigens have focused on a subset of gameto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(103 reference statements)
1
16
0
Order By: Relevance
“…Interestingly, when the IE membrane was removed from the gametocytes, human antibodies recognized native antigens expressed on the gametocyte membrane itself, consistent with other reports on permeabilized gametocyte-IEs (13). Major gametocyte surface antigens include Pfs230 and Pfs48/45, which are targeted by human antibodies and associated with transmission-blocking activity through mosquito feeding assays [reviewed in (9)].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, when the IE membrane was removed from the gametocytes, human antibodies recognized native antigens expressed on the gametocyte membrane itself, consistent with other reports on permeabilized gametocyte-IEs (13). Major gametocyte surface antigens include Pfs230 and Pfs48/45, which are targeted by human antibodies and associated with transmission-blocking activity through mosquito feeding assays [reviewed in (9)].…”
Section: Discussionsupporting
confidence: 90%
“…One study reported naturally-acquired antibodies recognized the surface of immature gametocyte-IEs (10). In contrast, other studies reported a lack of antibodies to immature stages, but some antibodies to mature stage V gametocyte-IEs (1113). The target of these antibodies is unknown.…”
Section: Introductionmentioning
confidence: 76%
“…Naturally occurring antibodies targeting Pfs230 and Pfs45/48 have been observed in field studies in The Gambia, Kenya, and Cameroon and were associated with reduced malaria transmission (30, 45). However, other studies reported that transmission reduction correlated with antibody responses to Pfs230 only (46) or with anti-Pfs48/45 antibodies only (6, 42, 43). These conflicting results may be due to differences in the history of exposure of study participants or existence of other co-infections.…”
Section: Naturally Acquired Antibody Responses To Gametocyte and Gamementioning
confidence: 90%
“…Second, it is not known what ingested antibody levels in the mosquito are required that would lead to a subsequent transmission blockade. The identification and validation of gametocyte surface antigens as vaccine candidates with transmission reducing activity (TRA) directly measurable in the human host will overcome these challenges, complement and strengthen current transmission blocking vaccine efforts (6, 52).…”
Section: Naturally Acquired Antibody Responses To Gametocyte and Gamementioning
confidence: 99%
See 1 more Smart Citation